Working from Home vs. In-office post-COVID-19: The End of a Seemingly Never-ending Debate? - Griszbacher, Norbert (GILE Journal of Skills Development, 2023)
The recent COVID-19 pandemic has swiftly and drastically transformed our daily lives, including our perception of working-from-home (WFH) practices. Even in a post-pandemic world, employees have shown an ardent desire to retain the benefits of the novel pandemic-induced remote work experience, which challenges managers to reintegrate them into the conventional office setting. This paper aims to assess the advantages and disadvantages of home and office work environments from the viewpoints of employees and employers to identify the optimal future scenario that maximises the benefits to all parties involved. Although our understanding of the optimal balance between remote and office work is limited, the future of work will involve a hybrid approach, combining remote and in-office work. The transition to such an arrangement demands time, creativity, trust, and various other factors from the parties. It also calls for serious mindset shifts and up/reskilling efforts. The review ends with a consideration of future scenarios and industry implications of adopting hybrid work.